2022
DOI: 10.1093/aje/kwac210
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Respiratory Infections From Birth to Young Adulthood

Abstract: We applied the population-based prospective Espoo Cohort Study (n=2,568) to identify potential susceptibility of subjects with asthma to respiratory tract infections (RTIs). Information on the occurrence of asthma and of both upper and lower respiratory tract infections (URTIs and LRTIs) was collected with a questionnaire at the baseline, the 6 year- and the 20 year-follow-up studies, and from the National Health Registries. We estimated age- and sex-specific incidence rate differences (IRD) and incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The susceptibility of subjects having asthma to catch respiratory infections has been shown in our recently reported study based on the Espoo Cohort Study from Finland, which reported that children and young adults having asthma experience increased risk of both URTIs with an adjusted incidence rate ratio (aIRR) 1.27 (95% CI 1.20 -1.35) and LRTIs with aIRR 2.87 (95% CI 2.33-3.53) up to the age of 27 years [5]. Although the mechanisms for such susceptibility are not yet fully understood, both immunological dysfunction and structural airway alterations observed in subjects having asthma are likely to play a role.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The susceptibility of subjects having asthma to catch respiratory infections has been shown in our recently reported study based on the Espoo Cohort Study from Finland, which reported that children and young adults having asthma experience increased risk of both URTIs with an adjusted incidence rate ratio (aIRR) 1.27 (95% CI 1.20 -1.35) and LRTIs with aIRR 2.87 (95% CI 2.33-3.53) up to the age of 27 years [5]. Although the mechanisms for such susceptibility are not yet fully understood, both immunological dysfunction and structural airway alterations observed in subjects having asthma are likely to play a role.…”
Section: Discussionmentioning
confidence: 84%
“…However, this could have biased the results towards more severe respiratory infections, so we did not conduct this analysis. Those with asthma have been suggested to be more susceptible to experience respiratory infections in general [4,5]. As this study was limited to those with recently diagnosed adult-onset asthma, comparison between different occupational groups can be considered valid, as although subjects in occupations related to increased rate of respiratory infections may later change their job due to this asthma-related susceptibility to infections, in the present study the majority of participants were still going through or had just gone through the diagnostic measurements for asthma when answering the FEAS questionnaire and the others had just recently received this diagnosis.…”
Section: Validity Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to maternal morbidities and in utero exposures, early-life exposures to respiratory viruses and bacteria, as well as environmental allergens, pollutants, and cigarette smoke have all shown an association with subsequent recurrent wheezing and asthma development (28)(29)(30)(31). In particular, the airway microbiome appears to play an important role in the development and phenotypic manifestations of asthma and allergy (32).…”
Section: Introductionmentioning
confidence: 99%
“…The amnion is also a source of epithelial cells that have been exposed to similar factors as the developing respiratory epithelium of the foetus/newborn [25][26][27]. In addition to maternal morbidities and in utero exposures, early-life exposures to respiratory viruses and bacteria, as well as environmental allergens, pollutants, and cigarette smoke have all shown an association with subsequent recurrent wheezing and asthma development [28][29][30][31]. One mechanism through which exposures appear to modulate future respiratory outcomes is through epigenetic reprogramming of host cells, with distinct methylation profiles being observed in respiratory epithelial cells from healthy, atopic, and asthmatic children [32].…”
Section: Introductionmentioning
confidence: 99%